Information Science in Transition. - Gilchrist, Alan (Facet Publishing, 2013)
Are we at a turning point in digital information? The expansion of the internet is unprecedented. Will information science become part of computer science and does rise of the term informatics demonstrate convergence of information science and information technology - a convergence that must surely develop? This work reflects on such issues.